The Effect of Capital, Establishment, Labor, and Education on Income Creative Industries (Case Study in Handicraft Industry Malang) - Wicaksana, Bangun Putra (Jurnal Ilmiah Mahasiswa FEB, 2016)
Creative industries have an important role in the economy of a region. Including in the city of Malang, in particular the creative industries in the handicraft sector. The important role of one of them is to expand employment. In Malang, there are four excellent creative industries subsector craft industry including furniture, industrial sanitary, rattan industry, and industrial ceramics. In the development of creative industries Malang craft sector need to be analyzed variables that affect the income of businesses. Variables which will be studied include capital, establishment, labor, and education. This study used secondary data obtained from the Central Bureau of Statistics, Department of Industry and  Trade  of  Malang,  Books,  Journals,  Internet  and  primary  data  through  direct  interview  to businesses with a questionnaire that had been prepared. Number of all the handicraft business into a superior product Malang is 119 business units. Then, using the formula Slovin taken 54 respondents businesses that became the object of study chosen by purposive sampling. To achieve the goal, in this research used multiple linear regression analysis and classical assumption. Based on calculations using SPSS 18, indicates that the variable capital (X1) Establishment (X2) labor (X3) and education (X4) with the same on the dependent variable (income (Y). It can be seen by test results  F  (simultaneously).  However,  based  on  the  t  test  (partial)  Establishment  has  no  effect significant on the level of income. The influence of independent variables (X1, X2, X3, X4) on the dependent  variable  (Y)  amounted  to  83.3%,  while 16.7%  Other  donated  by other  variables  not included in this equation.  Keywords: Creative Industry Handicraft Sector, Absorption Labor, Capital, Establishment, Labor, Education.